2016
DOI: 10.3402/iee.v6.32701
|View full text |Cite
|
Sign up to set email alerts
|

History and current status of peste des petits ruminants virus in Tanzania

Abstract: Peste des petits ruminants virus (PPRV) causes the acute, highly contagious disease peste des petits ruminants (PPR) that affects small domestic and wild ruminants. PPR is of importance in the small livestock-keeping industry in Tanzania, especially in rural areas as it is an important source of livelihood. Morbidity and case fatality rate can be as high as 80–100% in naïve herds; however, in endemic areas, morbidity and case fatality range between 10 and 100% where previous immunity, age, and species of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…This important position of small ruminants is one of the reasons behind the joint Food and Agriculture Organization (FAO) and World Organization for Animal Health programme to control and eradicate PPR and control small ruminant diseases [4]. PPRV is quickly increasing its spread across the world and is now threatening the most southern countries of Africa, with Tanzania currently being its southern border on the east coast [25]. To stop the spread further south, it is important to understand the prevalence and epidemiology of both PPR and its most common differential diagnosis, as the clinical presentation can be difficult to diagnose [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This important position of small ruminants is one of the reasons behind the joint Food and Agriculture Organization (FAO) and World Organization for Animal Health programme to control and eradicate PPR and control small ruminant diseases [4]. PPRV is quickly increasing its spread across the world and is now threatening the most southern countries of Africa, with Tanzania currently being its southern border on the east coast [25]. To stop the spread further south, it is important to understand the prevalence and epidemiology of both PPR and its most common differential diagnosis, as the clinical presentation can be difficult to diagnose [4].…”
Section: Discussionmentioning
confidence: 99%
“…PPR was first confirmed in Tanzania in 2008 [21], but a retrospective study on samples collected in the northern districts found antibodies to PPRV were probably already present in 2004 [22]. The disease has since spread to the southern parts of the country and is now considered endemic in the domestic, small ruminant population in the whole country [2325]. CCPP, FMD, BT, and BVD are endemic in Tanzania [24], however studies on FMD and BT have only been performed on large ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…The circulation of the disease across Eastern Africa was subsequently shown through the detection of the virus and/or of antibodies to PPRV in Kenya (1999), Uganda (2005 and 2007) and more recently in Tanzania (2010) (19)(20)(21)(22). PPR is nowadays widely spread in the whole of Africa and is endemic in most eastern African countries (2,23). In the Comoros archipelago, located in the Northern Mozambique Channel about 300 km of the southern coast of Tanzania (Figure 1), the first PPR outbreak occurred in 2012 (24).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the disease is characterized by high fever, oculo-nasal discharges, necrotizing and erosive stomatitis, diarrhoea, and dyspnea bronchopneumonia followed by either death or recovery from the disease (Balamurugan et al, 2012;Sharma et al, 2012;Jaisree et al, 2018). Animals that are unprotected by means of devoid of immunization has the morbidity rate can be up to 100% and mortality may be 20% to 90% particularly in goats (Torsson et al, 2016). In a study found that 74.13% morbidity and 54.83% mortality in Black Bengal goats in some selected areas of Bangladesh (Das et al, 2007).…”
Section: Introductionmentioning
confidence: 99%